Urban Drainage System Simulation Using 1D Model, Case Study: North Kembangan Drainage System, Jakarta - Putra, Rayhan Airlangga Wijanarko; Damarnegara, Satria; Savitri, Yang Ratri (Institut Teknologi Sepuluh Nopember, 2024)
Jakarta has a high level of urbanization, which causes land use changes and increasing inundation problems. One area that has experienced inundation is North Kembangan with a height of 20 - 30 cm in recent years and so of that the location is included in flood-prone sub-districts. Accordingly, a study is needed to estimate the North Kembangan drainage system actual conditions using the rainfall-runoff transformation model. This study simulates using the Storm Water Management Model (SWMM), and the calibration validation process is accomplished using the Nash-Sutcliffe model efficiency coefficient (NSE) and root mean square error (RMSE) method to evaluate the reliability of the model. The calibration for several model parameters is required to obtain the reliability model, including the channel Manning coefficient, land overflow Manning coefficient, and curve number. The calibration result shows that NSE values are 0,65, and the RMSE is 0,051 based on data in 2021. Then the validation result shows the NSE is 0,62 and RMSE is 0,040 based on data in 2022.